The trends of the cultural studies development in the modern conditions: the case of Ukraine - Pashkevych, Maryna; Shyber, Oksana; Kozlovska, Maryna; Semykras, Vasyl; Kabanets, Oleksandr; Korolenko, Ievgeniia (Multidisciplinary Science Journal, 2023)
The trends of cultural studies development in current conditions are analyzed in the article, with the case of Ukraine serving as an example. Cultural studies are gradually being transformed from an abstract sphere of philosophizing into a scientifically significant field. This transformation is supported by the review of candidate and doctoral dissertations, which demonstrate a shift towards applied science. The research in cultural studies adequately reflects the particularity of the current state of scientific practice, characterized by interdisciplinarity that significantly expands its potential for a flexible understanding of cultural practices. This transformation is driven by objective reasons, as the network of educational institutions, creative teams, concert venues, and other organizations in the field of music is the most extensive. It is asserted that cultural mentality, like any other type of mentality, is based on archetypes and embodied in myths. Cultural myths appeal to larger social mythological systems, leading to the transformation of cultural studies into the meaning of culture, which carries the imprint of corresponding chronotopes and worldviews. The current project is rooted in the idea of a total synthesis of cultures based on universals. In contrast, the postmodern project is motivated by the idea of deconstruction and the rhetoric of differences. Consequently, universalistic cultural studies tend to integrate various disciplines at the methodological level and aim to model the totality of world culture. On the other hand, particularistic cultural studies tend to reduce cultural studies to one of the components of cultural studies (typically aesthetics and art studies) at the methodological and subject levels, focusing on the investigation of individual components (genres, styles, ethnicities) of the phenomenon under study. The roots of cultural axiology can be traced back to the archetypal matrix of Greek-Orthodox thinking. It has provided strong traditions of cultural philosophy and its axiological reflection in Ukrainian humanistic thought. The traditional understanding of culture in Ukraine is deeply symbolic, axiological, and sacred.